(untitled) (Praxis Educativa, 2024)
This work deals with images of nature, their possible meanings and uses, within the framework of teacher training. For this, first the images included in the texts of the Moravian theologian and pedagogue Juan Amós Comenio (1592 -1670) and the place of nature - divine creation - as a pedagogical model are analyzed. Then, the work of the Brazilian artist and educator Rosana Paulino (1967) is presented, whose production questions the nature/humanity relationship in the West and calls for subverting the dichotomies of colonialist modernity. The counterpoint between both authors is an invitation to re-look at the images that come to us from tradition and to create, collectively, other/new/more images and imaginaries for education.